Children's experience in healthcare decisions: an overview - Lee, Siew Pien; Mohamad Shariff, Nurasikin (IIUM Press, 2018)
This article attempts to provide an overview of issues related to children’s participation in decisions relating to health care. It sets the discussion in the context of current debate about children’s participation in health care decisions and explores the extent to which children want to participate in the decision. This article concludes that children mostly occupy a minimal role in communication and decisions regarding their care. The patterns of participation of children in communication and decisions are differing and fluctuate between the children and within the same child throughout their hospitalisation, depending on the participating child, their preferences, and requirements at a particular time.